Abnormal BMI in Male and/or Female Partners Are Deleterious for Embryonic Development and Pregnancy Outcome During ART Process: A Retrospective Study - Qi, Lin; Liu, Ya-ping; Wang, Shi-ming; Shi, Hao; Chen, Xiao-li; Wang, Ning-ning; Su, Ying-chun (Frontiers in Endocrinology, 2022)
Objective: To investigate the effect of BMI in male and/or female partners on embryo development and clinical pregnancy outcome during ART Methods: Data of 11,130 cycles between January 2018 and December 2020 were retrospectively analyzed. They were divided into Group A, B, C, and D based on couples’ BMI values, also were divided into Group I, II, III and IV in IVF cycles and Group i, ii, iii, and iv in ICSI cycles. After grouping, inter-group indicators comparisons and logistic regression analysis were performed. Results: In IVF cycles, CPR in Group I and Group III were higher than Group IV. In Group III, it was higher than Group II. The AR in Group IV was higher, but the LBR was lower than Group I, Group II, and Group III. Logistic regression analysis results suggested that AR in Group IV was higher than that in Group I in IVF cycles, whereas LBR was lower. In ICSI cycles, high-quality embryo rate in Group i and Group ii were both higher than that in Group iii and Group iv. The CPR in Group i was higher than Group ii and Group iv, and in Group iii was higher than Group ii and Group iv. The AR in Group i was lower than Group iii and Group iv, and AR in Group ii was lower than Group iv. LBR, in Group I it was higher than Group ii, Group iii, and Group iv. Logistic regression analysis results suggested CPR in Group ii was significantly lower than that in Group i. AR in Group iii was considerably higher than that in Group i. LBR in Group ii and Group iv were significantly lower than that in Group i. Conclusion: Female higher BMI was not conducive to the formation of high-quality embryos in ICSI cycle. Female and/or male BMI affected AR and LBR more than CPR not only in IVF cycles, but also in ICSI cycles.